Effect of psychopharmacological combinations on psychopathological symptom burden and BMI trajectories in patients with eating disorders - Panarello, Ernesta; Monaco, Francesco; Di Stefano, Valeria; Vignapiano, Annarita; Zaffonte, Roberta; Pullano, Ilaria; Corrivetti, Giulio; Steardo, Luca; Fornaro, Michele (Frontiers in Psychiatry, 2026)
IntroductionEating disorders (EDs), particularly Anorexia Nervosa (AN), remain one of the most severe and treatment-resistant eating disorders, with high relapse rates and limited pharmacological options. While second-generation antipsychotics and antidepressants are commonly prescribed as adjuncts to nutritional rehabilitation, their real-world impact on weight restoration and psychopathological symptom severity remains unclear.MethodsWe conducted a prospective, naturalistic observational study of 127 inpatients diagnosed with restrictive anorexia nervosa (AN-r), binge–purge anorexia nervosa (AN-bp), or bulimia nervosa (BN). BMI and weekly psychopathological symptom burden were systematically monitored throughout a ten-week inpatient treatment program. Psychopharmacological treatments were recorded in real time, and the Average Morbidity Index (AMI), adapted from the Life Chart Methodology, was computed weekly as a prospective measure of clinical severity. Generalized Linear Models assessed the associations between specific drug classes and changes in BMI and AMI.ResultsPatients treated with mood stabilizers (e.g., Carbamazepine, Lithium) showed a smaller BMI increase compared to other groups (Coef. = –0.96 to –1.70; p< 0.05), suggesting a potential weight-stabilizing effect. Diazepam use was associated with greater weight gain (Coef. = +2.06; p = 0.02) but no clear benefit on AMI. Several antidepressants (e.g., Sertraline, Escitalopram) correlated with higher AMI scores, indicating less improvement in psychopathological symptom burden. Atypical antipsychotics (e.g., Olanzapine, Aripiprazole) were linked to greater reductions in AMI.ConclusionsProspective monitoring of BMI and AMI revealed differential associations between psychopharmacological agents and both nutritional and symptomatic trajectories in an inpatient ED cohort predominantly composed of patients with AN. Mood stabilizers were associated with smaller BMI increases, while several antidepressants corresponded to less improvement in psychopathological symptom burden. Atypical antipsychotics showed the strongest prospective reductions in AMI. These findings highlight the value of prospective, real-world monitoring to inform pharmacological strategies in treatment-resistant eating disorders.